A tailored nanocarrier DMON and CpGs synergistically drive the formulation of a highly immunogenic and long-acting vaccine against echinococcosis - Ting Xin; Xintao Gao; Siyi Tao; Chenghao Zhou; Zhifang Zhang; Jiabo Ding; Jiaxi Ru; Yinü Li (Materials Today Bio)
Hydatid disease (echinococcosis) is a zoonotic parasitic disease that seriously endangers human health and livestock production. To develop a safer, more effective vaccine with an exceptionally long-lasting immune response, we employed an ‘all-in-one’ strategy to construct a nanovaccine against echinococcosis. In this system, a dendritic mesoporous organosilica nanoparticle (DMON), Eg95 antigen, and two types of CpG potentiators (CpG ODN and pCpG) were integrated into a single nanoplatform. Compared to the commercial Quil-A-formulated vaccine, these two nanovaccines exhibited significant advantages in inducing early, robust, and long-lasting protective immune responses, especially in terms of IgG1 antibody responses and Th1 cytokine TNF-α secretion. Notably, the certain adjuvant combination (DMON + pCpG) formulated-vaccine Eg95N + pCpG@DMON conferred stronger adjuvanticity to the antigen than Quil-A during the late stage (42–84 days). Systematic evaluation demonstrated excellent biodegradability and biosafety of DMON and its-based vaccine. This research provides a strong foundation for upgrading vaccines against echinococcosis.